2014
DOI: 10.1007/s00419-014-0972-5
|View full text |Cite
|
Sign up to set email alerts
|

Tuning of a vibration absorber with shunted piezoelectric transducers

Abstract: In order to reduce structural vibrations in narrow frequency bands, tuned mass absorbers can be an appropriate measure. A quite similar approach which makes use of applied piezoelectric elements, instead of additional oscillating masses, are the well-known resonant shunts, consisting of resistances, inductances, and possibly negative capacitances connected to the piezoelectric element. This paper presents a combined approach, which is based on a conventional tuned mass absorber, but whose characteristics can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 14 publications
0
24
0
Order By: Relevance
“…Many authors [2][3][4][5][6][7][8][9][10][11][12][13][14] determined the parameters of an external electric circuit required for damping the specified vibration mode based on transfer functions of various kinds. It would be of considerable importance to compare the results obtained with the help of the transfer function with the results of solving the problem of natural vibrations of the structure in the proposed mathematical formulation.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many authors [2][3][4][5][6][7][8][9][10][11][12][13][14] determined the parameters of an external electric circuit required for damping the specified vibration mode based on transfer functions of various kinds. It would be of considerable importance to compare the results obtained with the help of the transfer function with the results of solving the problem of natural vibrations of the structure in the proposed mathematical formulation.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…where elements, respectively, and R q ; L p ; C r are the values of the inductance, resistance and capacitance of the corresponding circuit elements. For the problem of natural vibrations under zero-value boundary conditions (5,6,7), eigensolutions are sought in the following form: uðx; tÞ ¼ " uðxÞe iωt ; φðx; tÞ ¼ " φðxÞe iωt ; (14) where ω ¼ ω Re þ iω Im gives the complex natural vibration frequency, wherein ω Re corresponds to the circular natural vibration frequency, ω Im is the rate of its damping (the damping ratio of vibrations) and " uðxÞ; " φðxÞ are the natural vibration forms. Taking into account the form of solution (14), the variational equation for the problem of the natural vibrations of an electro-viscoelastic body with external electric circuits in the case of an absence of external loads takes the following form:…”
Section: Mathematical Statement Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of the literature showed that in terms of efficiency of finding the appropriate parameters for external circuits providing passive vibration damping, this approach is still most popular when analyzing the dynamic behavior of electroelastic systems with external electric circuits. In this case, the optimal values of the external circuit parameters estimated on the basis of the transfer functions can be obtained by different ways, for example, by optimizing the transfer functions with respect to 2  -or  -norms [8,17], assuming the equality of amplitudes of transfer functions at the characteristic intersection points of curves [2,6,10], using the technique for placing the poles of the transfer function ( pole placement technique) [9][10]18], etc. The result of all these peculiarities is that, depending on the ways of constructing the transfer function and selecting the optimization criterion, the optimal parameters of the external circuit parameters can take different values [2,10,17].…”
Section: Introductionmentioning
confidence: 99%
“…By using active circuits to realize negative capacitances, a broad adaptation frequency range can be realized. However, the active circuits have to be designed with respect to the high voltages that occur at the piezoelectric elements, which still remain a challenge [19].…”
Section: Vibration Analysis and Control In Mechanical Structures And mentioning
confidence: 99%